ANALYSIS OF URBAN FORM DYNAMICS BASED ON LAND COVER DEVELOPMENT MODELING USING CA-AHP AND ITS IMPLICATIONS ON THE SPATIAL PLANNING OF SUBANG REGENCY - Utsman Siddiq, Ahmad
The development of land coverage in Subang District shows that there is an increase in the need for built-up land due to the rapid development of transportation infrastructure and industrialization. The conversion of this land can cause a decline in the quality of the environment. Therefore, the purpose of this study is to investigate the development of land coverage in Subang District in 2031 based on a quantitative calculation of the urban form metric and a modeling of the development of land coverage that will occur based on predetermined factors and weights calculated using the AHP method. The factors identified as influencing the development of land coverage in Subang District are the distance factor from: Toll Road, Artery, Collector, Patimban Port, Built-up Land, Large Industry, Activity Center, Water Agency, and Slope. Based on the calculation of factor weights using the AHP method, it was identified that the distance factor from Patimban Port is the most important factor with score of 0.2365. The results of modeling the development of land coverage with an overall accuracy of 90%, show that the type of land coverage that is most commonly converted to built up is land coverage crops with a conversion distribution for scenario 1 occurring in more areas of Binong, Cibogo, Ciasem, and Pamanukan districts, while in scenario 2 it tends to be located in Pusakanagara, Cipendeuy, Cipunagara, Pamanukan and Cibogo districts. Based on this model, the level of compatibility with the Land Use Plan was 60.62% in scenario 1 and 66.01% in scenario 2. When compared to the Land Use Plan, this results in a compatibility gap of 47.23% in scenario 1 and 35.86% in scenario 2. This indicates that scenario 2 has a higher level of compatibility than scenario 1. With this compatibility gap, it can be identified that there are still lands that are simulated to be converted but are not yet accommodated in the Land Use Plan. The results of modeling the development of land coverage are then used as a basis for the quantitative calculation of the urban form metric, which shows that the characteristics of the Urban Form in 2031 will develop with a higher patch density level, closer and more connected distances between patches, and a more regular patch shape index. This shows that the dynamic characteritstic of the Urban Form in Subang District in 2031 will tend to be more compact, dense, and connected. This shows that the dynamic pattern of the Urban Form that is formed tends towards a pattern of compact Urban Form development. In relation to the type of urban form dynamics, it was found that there is a type of aggregation built-up land coverage expansion pattern that forms a ribbon pattern that develops on the toll road and Jatibarang-Kadipaten & Pantura arterial road, while in scenario 1 the ribbon pattern develops on the toll road & Pantura arterial road. It was also found that there is a fragmentation dynamic type that has a leapfrog pattern where this pattern occurs randomly and spreads outside the locations experiencing built-up land coverage development based on modeling results.